Analysis of the spatial patterns in localization of gold mineralization relative to the system of deep faults in the Chortomlyk greenstone structure of the Ukrainian shield - Zhiltsova I.V.; Ruzina M.V.; Malova M.L.; Bilan N.V.; Tereshkova O.A.; Gardysh A.S. (Днепропетровский национальный университет им. Олеся Гончара, 2018)
The results of analysisof the patterns of the spatial relationship between hydrothermal gold ore formations and the zones of metasomatites and systems of deep faults within the Chortomlyk greenstone structure of the Middle Pridniprovie megablock in the Ukrainian Shield are given. As a result of studying the localization conditions of gold mineralization, it was established that the gold-bearing mineralization is confined to tectonically fractured zones and is localized among metasomatically altered rocks. The hydrothermal series of metasomatites in the Chortomlyk greenstone structure is represented by greisens, propylites, amphibole-carbonate metasomatites and listvenite-berezites. The mineralization of Au and Mo is associated with metasomatites of the greisen type. The study of spatial relationship between the fields of metasomatites and the gold mineralization and zones of deep faults revealed that the closest relationship is expressed with systems of faults with azimuths of 0° and 270°, 17° and 287°, 77° and 347°. The results of the studies allowed us to develop a new prospecting criterion, which, in turn allows us to state that the gold mineralization within the Chortomlyk greenstone structure is spatially confined to metasomatites related to the schistosity, fracture, millonitization, and cataclase zones with high content of sulphide mineralization. These zones are localized in nodes of intersecting faults of the first order of the system 77° and 347° with discontinuous violations of high orders of azimuths of 0° and 270°, 17°and 287°. The results of the research can be used to develop a set of predictive criteria and the allocation of promising sites of hydrothermal mineralization of gold within the Chortomlyk greenstone structure of the Middle Pridniprovie megablock in the Ukrainian shield.
Keywords: deep faults; metasomatite; gold mineralization; greenstone structure; Middle Pridniprovie megablock; hydrothermal formations; глибинні розломи; метасоматити; мінералізація золота; зеленокам'яна структура; Середньпридніпровський мегаблок; гідротермальні формації